Dampak Penerapan Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan - Wardani, Widi; Nirawati, Yohana Ayu; Djasuli, Mohamad (CV. ITTC INDONESIA, 2022)
In Indonesia, the National Committee on Governance Policy (KNKG) aims as a response to the occurrence of the financial crisis in Asia which, according to the World Bank, occurred due to poor implementation of corporate governance which is considered the worst crisis in Asia. Bankruptcy of a company can be measured by the financial statements issued by the company, the company's financial statements are a source of information about the company's financial position. The impact of implementing Good Corporate Governance on company performance is the key to success for companies to gain profits. One mechanism that is expected to control agency costs is by implementing good corporate governance. Financial reports made with accounting numbers are expected to minimize conflicts between interested parties.